2013
DOI: 10.1089/jwh.2012.4123
|View full text |Cite
|
Sign up to set email alerts
|

Laxity of the Vaginal Introitus After Childbirth: Nonsurgical Outpatient Procedure for Vaginal Tissue Restoration and Improved Sexual Satisfaction Using Low-Energy Radiofrequency Thermal Therapy

Abstract: A single nonsurgical office-based RF procedure for vaginal introital laxity achieved significant and sustainable 12-month effectiveness with respect to improved integrity at the vaginal introitus and improved sexual satisfaction. Treatment was well-tolerated with no adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 29 publications
1
69
0
2
Order By: Relevance
“…The use of the RF to treat facial and body skin laxity also has demonstrated clinical response positive, (13,14,15,16,17,18) however, in the literature there is a lack of studies that evaluate the therapeutic response of RF in laxity tissue of the labia majora. In this study, 100% of patients reported satisfaction with the appearance of their genitalia after treatment with RF.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the RF to treat facial and body skin laxity also has demonstrated clinical response positive, (13,14,15,16,17,18) however, in the literature there is a lack of studies that evaluate the therapeutic response of RF in laxity tissue of the labia majora. In this study, 100% of patients reported satisfaction with the appearance of their genitalia after treatment with RF.…”
Section: Discussionmentioning
confidence: 99%
“…Através do aumento da temperatura, a radiofrequencia estimula a prodção de novos colagenos, fazendo com que a regiao vaginal modifique suas caracteristicas melhorando a função sexual, principalmente nos desfechos de dor na relação e dificuldade para atingir o orgasmo 18,19,20 .…”
Section: Conflitos De Interessesunclassified
“…Emission of electromagnetic energy of variable wavelength aims at anatomical re-modelling and rejuvenation of extraintroital and extra-vaginal tissues through thermal re-activation of fibroblasts [10][11][12]. Immunohistochemical and electron microscope observations are steadily accumulating that correlate fibroblast reactivation and deposition of new networks of collagen and elastin fibres in the subepithelial layers of the vulva.…”
Section: Introductionmentioning
confidence: 99%